Development and validation of a point-of-care breath test for octane detection - Hagens, LA; Verschueren, ARM; Lammers, A; Heijnen, NFL; Smit, MR; Nijsen, TME; Geven, I; Schultz, MJ; Bergmans, DCJJ; Schnabel, RM; Bos, LDJ (Royal Society of Chemistry, 2021)
Background: There is a demand for a non-invasive bedside method to diagnose Acute Respiratory Distress Syndrome (ARDS). Octane was discovered and validated as the most important breath biomarker for diagnosis of ARDS using gas-chromatography and mass-spectrometry (GC-MS). However, GC-MS is unsuitable as a point-of-care (POC) test in the intensive care unit (ICU). Therefore, we determined if a newly developed POC breath test can reliably detect octane in exhaled breath of invasively ventilated ICU patients.